Rethinking Medical Diplomacy as a Part of the Public Diplomacy: The Case of China - Rara Shertina; Ario Bimo Utomo (Nusantara Science and Technology Proceedings, 2022)
This article reviews China's efforts to provide medical assistance during the Covid-19 pandemic. Here, the author uses the point of view that this assistance can be categorized as a public diplomacy effort because it is aimed at people in foreign countries. This article attempts to broaden the definition of medical diplomacy which leads to public diplomacy. This was found by the author after analyzing the impact of Chinese diplomacy on the image of his country and linking it to China's medical diplomacy efforts that had been carried out.